Diagnosing and Treating Extrapulmonary Tuberculosis in India: Challenges and Solutions - Neeraj Nischal; Ravindra Nath; Vidushi Rathi; Pranav Ish (Preventive Medicine: Research & Reviews, 2024)
Tuberculosis (TB) is a major health problem in India. The focus is on pulmonary TB (PTB), extra-PTB (EPTB) remains a challenge for both diagnosis and treatment. This review discusses the challenges and solutions for effectively managing EPTB in India. The INDEX-TB guidelines for EPTB, developed by the All India Institute of Medical Sciences in New Delhi, hold significant importance for the effective management of EPTB cases. To enhance the diagnosis of EPTB in India and globally, a multifaceted approach should be adopted, engaging governments, healthcare systems, research institutions and local communities.